Formulation and Evaluation of Ledipasvir Nano-suspension Through QbD Approach - Rahman, Md Rezowanur; Shill, Diponkor Kumar; Kumar, Uttom; Hossain, ASM Monjur Al; Bachar, Sitesh Chandra; Rouf, Abu Shara Shamsur (Dhaka University Journal of Pharmaceutical Sciences, 2023)
Ledipasvir, belonging to the BCS class II, is a directly acting anti-viral agent used to treat Hepatitis C virus infections. Due to poor water solubility and oral bioavailability, developing an effective delivery system for this drug has been an enormously challenging issue for the formulators. Moreover, suitable dosage forms for pediatric and geriatric patients and patients having difficulty in swallowing as well pose an added burden. Therefore, the present study aims to formulate a nanosuspension, via a solid dispersion technique, based on liquid oral suspension using the Quality by Design (QbD) method. Primarily, the compatible polymers for Ledipasvir were screened using FT-IR and DSC, and finally, the polymers- poloxamer 188, poloxamer 407, HPC and HMPC were selected, considering their ability to turn the API into amorphous state in solid dispersions. The design of formulation and analysis with the D-Optimal design using Design Expert® Software revealed that poloxamer 188 and poloxamer 407 at 0.3:0.7 ratio of Ledipasvir:Polymer produced the optimized nanosuspension formulations with a statistically significant mathematical model. Subsequently, the formulations were stabilized using a suspension vehicle optimized via Box-Behnken design using the amount of xanthan gum (gm), avicel® RC-591 (gm) and citric acid monohydrate (gm) as independent variables, and viscosity (cp) and zeta potential (mv) as responses. The dissolution profiles revealed that the prepared suspensions of Ledipasvir had much faster dissolution than the market products available as the tablet dosage form. In-vivo simulation studies using PKSolver® suggested that the absorption of the drug from the formulated suspensions was comparable to that of market product up to a single dose level (90 mg) and superseded in triplicate dose level (270 mg). The formulated suspensions were found to be stable over three- and six-month periods, as identified via accelerated stability studies. Interestingly, the dissolution profile of the stabilized suspensions was found to be similar after six months to that of the initial. Dhaka Univ. J. Pharm. Sci. 22(2): 173-188, 2023 (December)